Novel manganese and polyester dendrimer-based theranostic nanoparticles for MRI and breast cancer therapy. Issue 3 (21st December 2022) - Zhou, Xiaoxuan; Xu, Xiaodan; Hu, Qiuhui; Wu, Yan; Yu, Feidan; He, Chengbin; Qian, Yue; Han, Yuxin; Tang, Jianbin; Hu, Hongjie
Abstract : A manganese-based and hypericin-loaded polyester dendrimer nanoparticle (MHD) is reported for magnetic resonance imaging (MRI) and hypericin-based photodynamic therapy (PDT). Abstract : Therapeutic nanoplatforms are widely used in the diagnosis and treatment of breast cancer due to the merits of enabling high soft-tissue resolution and the availability of numerous therapeutic nanoparticles. It is thus vital to develop multifunctional theranostic nanoparticles for the visualization and dynamic monitoring of tumor therapy. In this study, we designed a manganese-based and hypericin-loaded polyester dendrimer nanoparticle (MHD) for magnetic resonance imaging (MRI) and hypericin-based photodynamic therapy (PDT) enhancement. We found that MHD could greatly enhance MRI contrast with a longitudinal relaxivity of 5.8 mM −1 s −1 due to the Mn-based paramagnetic dendrimer carrier. Meanwhile, the MRI-guided PDT inhibition of breast tumors could be achieved by the hypericin-carrying MHD and further improved by Mn 2+ -mediated alleviation of the hypoxic microenvironment and the enhancement of cellular ROS. Besides, MHD showed excellent biocompatibility and biosafety with liver and kidney clearance mechanisms. Thus, the high efficiency in MRI contrast enhancement and excellent tumor-inhibiting effects indicate MHD's potential as a novel, stable, and multifunctional nanotheranostic agent for breast cancer.